INOKULASI GANDA RHIZOBIUM DENGAN CENDAWAN ARBUSCULAR MIKORIZA PADA BANGKUANG - Iswandi Anas; T Yulliawati; J Heinzemann (Jurnal Ilmu Tanah dan Lingkungan, 1999)
Single inoculation with respectively three strains of Rhizobium (Ci-1, Ci-2, Ci-3) and two strains of arbuscular mycorrhizal fungi (78-1 and 41-3) as well as their double inoculation had been tested for their effectiveness in increasing the growth of yam bean (Pachyrhizus erosus) in a greenhouse experiment. This study was conducted at the Laboratory of Soil Biology, Department of Soil Sciences, Faculty of Agriculture, Bogor Agricultural University (IPB) Bogor. The results showed that all Rhizobium inoculation did not increase the growth of yam bean. On the other hand, inoculation with two strains of arbuscular mycorrhizal fungi increased the plant growth significantly (4 times for strain 78-1 and 1.46 time for 41-3). Double inoculation between three Rhizobium strains and two of arbuscular mycorrhizal fungi strains (78-1 and 41-3) was not significantly different from a single arbuscular mycorrhizal fungi inoculation (78-1 or 41-3).